Performance and economic evaluation of a photovoltaic/thermal (PV/T)-cascade heat pump for combined cooling, heat and power in tropical climate area - Rithy Kong (2020)
© 2020 The Authors Performance analysis of a new PV/T-cascade heat pump design having 7-kW maximum cooling capacity for combined cooling, heat and power was simulated with the climate of Chiang Mai, a city in tropical area. The technique could enhance both electrical performance of PV/T module, and heat pump thermal performance for cool water (below 17°C) and hot water (80-90°C) generations. Part of the cool water generated by the heat pump was used to cool down the PV/T module temperature and increase the PV/T generated electrical power. In addition, the heat from the PV/Ts became additional cooling load of the heat pump then the cooling and heating capacities of the heat pump could be increased. The unit was used to replace the existing units, a hot water electrical heating system and a vapor-compression chilled water system. With the electrical power generated by a set of PV/T modules, the new unit could save the grid electrical consumption significantly. From economic assessment with 10-hour daily operating time (7:00-17:00), the suitable PV/T module number each of 200 Wp (peak power) was found to be 7. It could also be found that 23.76 × 103 kWhe of the annual grid electrical energy was saved and the payback period of the unit was 7.87 years.